Asymmetric synthesis of a highly functionalized beta-amino acid: the key amino acid of sperabillins B and D - Davies, S; Ichihara, O (1999)
The asymmetric synthesis of the highly functionalized (3R,5R,6R)-3,6-diamino-5-hydroxyheptanoic acid, the key amino acid fragment of sperabillins B and D, was achieved by an asymmetric Michael addition of lithium (R)-(α-methylbenzyl)allylamide 10 to (E,E)-2,5-heptadienoate establishing the C-3 stereogenic centre, the information from which was propagated to the C-5 and C-6 centres by a highly stereoselective iodocyclocarbamation reaction.